Parkinson’s disease models and death signaling: what do we know until now? - Pedrão, Luiz Fernando A. T.; Medeiros, Pamela O. S.; Leandro, Estela C.; Falquetto, Barbara (Frontiers in Neuroanatomy, 2024)
Parkinson’s disease (PD) is the second neurodegenerative disorder most prevalent in the world, characterized by the loss of dopaminergic neurons in the Substantia Nigra (SN). It is well known for its motor and non-motor symptoms including bradykinesia, resting tremor, psychiatric, cardiorespiratory, and other dysfunctions. Pathological apoptosis contributes to a wide variety of diseases including PD. Various insults and/or cellular phenotypes have been shown to trigger distinct signaling events leading to cell death in neurons affected by PD. The intrinsic or mitochondrial pathway, inflammatory or oxidative stress-induced extrinsic pathways are the main events associated with apoptosis in PD-related neuronal loss. Although SN is the main brain area studied so far, other brain nuclei are also affected by the disease leading to non-classical motor symptoms as well as non-motor symptoms. Among these, the respiratory symptoms are often overlooked, yet they can cause discomfort and may contribute to patients shortened lifespan after disease diagnosis. While animal and in vitro models are frequently used to investigate the mechanisms involved in the pathogenesis of PD in both the SN and other brain regions, these models provide only a limited understanding of the disease’s actual progression. This review offers a comprehensive overview of some of the most studied forms of cell death, including recent research on potential treatment targets for these pathways. It highlights key findings and milestones in the field, shedding light on the potential role of understanding cell death in the prevention and treatment of the PD. Therefore, unraveling the connection between these pathways and the notable pathological mechanisms observed during PD progression could enhance our comprehension of the disease’s origin and provide valuable insights into potential molecular targets for the developing therapeutic interventions.